Efficient and innovative method for simultaneous detection of doping-prohibited substances in herbal medicines using LC-MS/MS - Lee, Hyeon-Jeong; Park, Saeyeon; Cho, Yoeseph; Park, Hana; Heo, Soohyun; Hwang, Sungmin; Moon, Jihwan; Lee, Dong-Woo; 손정현 (제73회 한국분석과학회 추계학술대회 [초록집], 2024)
Contrary to the common perception that herbal medicines are safe, some herbs have been found to contain doping-prohibited substances, which might lead to unintentional doping in athletes. This study aimed to develop and validate a rapid pretreatment method for the simultaneous detection of approximately 200 doping-prohibited substances in herbal medicines using liquid chromatography-tandem mass spectrometry with a triple quadrupole (LC-MS/MS). The extraction procedure was optimized by adjusting extraction salt conditions, solvent types, and elution parameters. The clean-up process was optimized using various individual sorbents and sorbent combinations. The optimization of the pretreatment method was analyzed using LC-MS/MS for the target substances. In the extraction step, the overall recovery of the target substances improved with DW and 50% ACN in the absence of extraction salts, compared to using a combination of six different extraction salts. Since the approximately 200 target substances comprised polar and non-polar compounds, sequential extraction with polar and organic solvents was applied to achieve complementary recovery. Following the sequential extraction, the subsequent clean-up step obtained satisfactory recovery using PSA and C18EC sorbents. The developed method was validated by international guidelines, demonstrating high sensitivity, specificity, and reproducibility. This methodology could be applied to monitor approximately 200 doping-prohibited substances from herbal medicines to prevent unintentional doping in athletes.